PENGARUH NET PROFIT MARGIN DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2022 - Silviana, Ratu; Mutawali (Journal of Research and Publication Innovation, 2024)
Indonesian mining has existed since the Hindu Buddhist era and continues to grow and show profitable results. This sector also has an attraction for investors, along with the process of buying and selling shares in Indonesia is increasingly widespread. Therefore, stock trading is one of the important components in driving Indonesia's economic growth, so that investor interest in investing in the mining sector is very large. Therefore, this reason makes the author interested in conducting research on the mining sector. Where this study aims to determine the effect of Net Profit Margin (NPM) and Earning Per Share (EPS) variables on Stock Price. This study uses secondary data which is quantitative in nature. The sampling technique used is purposive sampling. The analysis method used is panel data regression analysis using the eviews version 12 application and using the financial statements of 4 mining sector companies from 2013-2022 as research samples.  Based on the results of the study, it can be concluded that Net Profit Margin has a positive effect on stock prices, this is evidenced by (tcount 4.926911> ttable 2.02439) Earning Per Share (EPS) partially has no significant effect on Stock Price, this is evidenced by (tcount -1. 204839 < t table 2.02439) and simultaneously Net Profit Margin (NPM) and Earning Per Share (EPS) affect the Share Price of mining companies listed on the Indonesia Stock Exchange by 36% in 2013-2022, this is evidenced by (Fhitung 11.89034 > Ftabel 3.252).